Alznerisches Verb aus synchroner Sicht - Dolatowski, Marek (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
The article presents the Halcnovian verb from the synchronic point of view. In its first part it contains the description of the Halcnovian ethnolect and its history. Then, the morphology of the Halcnovian verb is analysed. The methodology has been taken from the Linguistisches Analysemodell of Józef Darski. The author describes both the basic forms (for example: infinitive, past participle, paradigms of the present and past tense) and complex constructions (for example: perfect, future, passive voice); there are also given numerous examples to each analysed phenomenon. In the last part the syntax of verbal constructions is presented: mainly the position of the finitum and the potential finitum in simple and complex phrases is considered. In addition, there is shortly presented also the research project “Dziedzictwo językowe Rzeczypospolitej. Baza dokumentacji języków zagrożonych” (“Poland’s Linguistic Heritage. Documentation Database for Endangered Languages”), because the ethnolect is explored in its context.Ein wissenschaftliches Projekt finanziert im Rahmen des Programms des Ministers für Wissenschaft und Hochschulwesen „Nationales Programm zur Entwicklung der Humanistik“ in den Jahren 2012–2013.